Malaysia Company Law: Principles and Practice - Aiman Nariman Mohd Sulaiman, Effendy Othman (Wolters Kluwer, 2015)
this book is an invaluable teaching and learning tool and provides practical insight into understanding company law for students as well as legal practitioners and professionals in management and finance related matters